THE INFLUENCE OF BRAND IMAGE AND PROMOTION ON THE PURCHASE DECISION OF INCOE CAR BATTERY BATTERIES AT CV RIAU'S SUCCESS DINAMO - Haji Mustaqim; Raja Amra W; Darmawan Indra Perdana Kesuma (PENANOMICS: International Journal of Economics, 2023)
The purpose of this study was to determine the effect of brand image and promotion on purchasing decisions for Incoe brand car batteries at CV Riau Sukses Dinamo. The place of this research was carried out at CV Riau Sukses Dinamo. The number of samples in this study were 97 consumers using the incidental sampling technique. The data collection method in this study was a questionnaire using multiple linear analysis.Based on the results of the study, the results of multiple linear analysis yielded a value of Y = 23,103 + 0,305 X1 + 0,421 X2, and the results of the t test were equal to Brand Image (X1) using the t test with t count = 4,752 > t table 1,985. Promotion (X2), produces t count = 7,074 > t table 1,985. The results of the F test, F count > F table (104,665 > 3.09) and a significance level of 0.000 <0.05 and the results of the coefficient of determination test yield Adjusted R Square = 0.684, meaning 68.4% simultaneously with Brand Image (X1) and Promotion (X2) variables ) contributes to the variable Purchase Decision (Y) of 68.4%, the remaining 31.6% is influenced by other factors not observed in this study.